Dynamic response of RNA editing to temperature in grape by RNA deep sequencing - Zhang, Aidi; Jiang, Xiaohan; Zhang, Fuping; Wang, Tengfei; Zhang, Xiujun (Functional & integrative genomics, 2020)
RNA editing is a post-transcriptional process of modifying genetic information on RNA molecules, which provides cells an additional level of gene expression regulation. Unlike mammals, in land plants, RNA editing converts C-to-U residues in organelles. However, its potential roles in response to different stressors (heat, salt, and so on) remains unclear. Grape is one of the most popular and economically important fruits in the world, and its production, like other crops, must deal with abiotic and biotic stresses, which cause reductions in yield and fruit quality. In our study, we tested the influence of the environmental factor temperature on RNA editing process in the whole mRNA from grape organelle. In total, we identified 122 and 627 RNA editing sites in chloroplast and mitochondria respectively with the average editing efficiency nearly ~ 60%. The analyses revealed that number of non-synonymous editing sites were higher than that of synonymous editing sites, and the amino acid substitution type tends to be hydrophobic. Additionally, the overall editing level decreased with the temperature rises, especially for several gene transcripts in chloroplast and mitochondria ( matK , ndhB , etc.). We also found that the expression level of most PPR genes decreased with the temperature rises, which may contribute to the decline of RNA editing efficiency at high temperature. Our findings suggested that the RNA editing events were very sensitive to heat stress; the changes of amino acid in RNA editing genes may contribute to the stress adaption for grape.